Compliance with the social and environmental development programs of the Minera Barrick company in the Pierina-Huaraz Production Unit - Orihuela Salazar, Luis Alfredo (2021)
The research carried out proposed analyzing the impact on the implementation of the social and environmental development programs of the Minera Barrick company, for which the Pierina-Huaraz Production Unit focused. For this, an elementary type of investigation was used, making use of an investigative design of a quantitative nature, in strict compliance with academic rigor. The universe considered in the present study was the community of Cuncashca, Mareniyoc, Mataquita and Atupa, corresponding to Jangas, belonging to Huaraz which have a population of 767 inhabitants, distributed in 330 homes, for which in reference to the study, it was considered a sample of 75 families from nearby towns, applying an instrument of 15 dichotomous questions, which I take into consideration are those related to the significant contributions that are provided to neighboring communities, corresponding to sustainability indicators, as well as the relationship positive and symbiotic with the neighboring commune. The most remarkable findings are to be found, for the Cuncashca community 75% indicate that through the PIRSA Program implemented by the mining company firm steps were taken towards the sustainability of development, which is undertaken by the Barrick company, in the same way a 72.5% of Mareniyoc community respondents point out the same as 65.5% from Atupa and 63.5% respectively from Mataquita. It is also important to mention for the sake of truth and the necessary transparency in any scientific research process that a small percentage of residents of the areas surrounding the mining settlement expressed that the support from the mining authorities was not adequate. In each nearby community, the results obtained showed that there is a sector of said population that does not recognize the contribution of the mining company, however, the large percentage expressed that there is. Therefore, it is concluded that the scope of the mining company's programs translates into sustainable investment projects, and an incentive that goes beyond the purely economic aspect, since it is seriously focused on the search to provide better living conditions to the population while laying the foundations for sustainable development for all the communes surrounding the mining settlement focused in the framework of the study.